2022
DOI: 10.1038/s41588-022-01182-0
|View full text |Cite
|
Sign up to set email alerts
|

The NALCN channel regulates metastasis and nonmalignant cell dissemination

Abstract: We identify the sodium leak channel non-selective protein (NALCN) as a key regulator of cancer metastasis and nonmalignant cell dissemination. Among 10,022 human cancers, NALCN loss-of-function mutations were enriched in gastric and colorectal cancers. Deletion of Nalcn from gastric, intestinal or pancreatic adenocarcinomas in mice did not alter tumor incidence, but markedly increased the number of circulating tumor cells (CTCs) and metastases. Treatment of these mice with gadolinium—a NALCN channel blocker—si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…Loss of NALCN promotes cancer metastasis. A dramatic increase in cancer metastasis with the deletion of NALCN in mice validates NALCN lossof-function is a significant cancer metastasis driver (Rahrmann et al, 2022). Deleting NALCN from normal gastric stem cells, upregulation of epithelial-mesenchymal transition and invasion genes were observed within 72 h (Rahrmann et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Loss of NALCN promotes cancer metastasis. A dramatic increase in cancer metastasis with the deletion of NALCN in mice validates NALCN lossof-function is a significant cancer metastasis driver (Rahrmann et al, 2022). Deleting NALCN from normal gastric stem cells, upregulation of epithelial-mesenchymal transition and invasion genes were observed within 72 h (Rahrmann et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…Mutations of NALCN in human cancer at a similar frequency of TP53, suggesting that NALCN could act as a tumor suppressor (Joerger and Fersht, 2016). Recently, Eric P. Rahrmann et al found that trafficking of epithelial cells to distant tissues is regulated by NALCN, and loss of NALCN promotes cancer metastasis (Rahrmann et al, 2022). However, no comprehensive pan-cancer analysis of NALCN has been conducted.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations